Students: digital natives or residents and digital visitors? - Julio Cabero-Almenara; Julio Barroso-Osuna; Sandra Martínez-Pérez (Opción, 2021)
This research emphasizes identifying two types of patterns of people: visitors and residents. An exploratory study was carried out to find out how students are perceived in the digital age, on two planes: personal and professional. An "ad hoc" instrument was elaborated and administered in the subject "Educational Technology" of the Pedagogy degree of the University of Seville. As results, despite the fact that most of them see themselves as residents, the perceptions disagree with the evidence obtained from the graphic representations made.